What Is Moral Competence and Why Promote It? - Nowak, Ewa (ETHICS IN PROGRESS, 2016)
This short review paper focuses on Georg Lind's approach to the moral competence as described in his recent book (2016) How To Teach Morality? Promoting Deliberation and Discussion, Reducing Violence and Deceit. Berlin: Logos Verlag. Lind's dual-aspect approach is discussed as one of the leading conceptions of personal moral competence and moral cognition today. Intuitionist approach and "embodied cognition" are not enough, the author (E. Nowak) claims. As participants of social contexts and institutions, we need manifest, discoursively articulated reflection, self-reflection, and conversation. However, Lind's hypothesis of two leyers of morality, i.e., a conscious and unconscious finds evidence in cognitive sciences too. Lind's approach is not as reductionist as that of radical cognitivists. On the contrary, it combines all relevant aspects of moral cognition discussed right now, worldwide – when cognitive sciences flourish and the challenges for moral mind grow up dramatically.